Morphometric evaluation and planning of anticurvature filing in roots of maxillary and mandibular molars - Maria Antonieta Veloso Carvalho OLIVEIRA; Jessyca Figueira VENÂNCIO; Luís Henrique Araújo RAPOSO; Nelson BARBOSA JÚNIOR; João Carlos Gabrielli BIFFI (Sociedade Brasileira de Pesquisa Odontológica, 2015)
This study aimed to guide the planning of anticurvature filing using pre-determined anatomical points on teeth to establish directions for proper implementation of the technique. Two hundred digital periapical radiographs of human molar teeth were selected and divided into two groups (n = 100): MX (maxillary) and MD (mandibular) molars. Mesiobuccal roots were considered for the MX group and mesial roots for the MD group. Pre-determined anatomical points required for planning the anticurvature filing on the root canal path were located, and the distances between these points obtained. The anticurvature filing was simulated in two different protocols for each group, and the region of dentin removal and the remaining dentin thickness were measured in the safety and danger zones of the root canals. Statistical analysis was carried out at a significance level of 5%. The distances between the anatomical points and the thickness of remaining dentin showed significant differences when the two groups were compared (p < 0.001). No significant differences were found between the two experimental groups regarding the area of dentin removal at the root region, but differences were detected in comparison with dentin removal at the crown (p < 0.001). In terms of wear produced after simulation of both anticurvature filing protocols, significant differences were verified for all regions, except for the dentin remaining at the danger zone. The radiographic location of anatomical points allows for planning and implementation of controlled and efficient anticurvature filing and can be performed in the same manner for maxillary and mandibular molars.